Aesthetic experience of dance performances - Vukadinović, Maja (Drustvo Psihologa Srbije, 2018)
In this study the aesthetic experience of dance performances is investigated. The study includes construction of an instrument for measuring the aesthetic experience of dance performances and an investigation of the structure of both dancers’ and spectators’ aesthetic experience. The experiments are carried out during eight different performances of various dance forms, including classical ballet, contemporary dance, flamenco and folklore. Three factors of aesthetic experience of dance performances are identified: Dynamism, Exceptionality and Affective Evaluation. The results show that dancers’ aesthetic experience has a somewhat different factorial structure from that of the spectators’. Unlike spectators’ aesthetic experience, dancers’ aesthetic experience singles out the Excitement factor. The results are discussed within the context of dancers’ proprioception and spectators’ exteroception since these findings confirm the idea of a significant role of proprioception in dancers’ aesthetic experience.